Analysis of Non-Yielding Basement Wall Adjacent to Strip Footing - Touqan, Majid Omar (2016)
A Master of Science thesis in Civil Engineering by Majid Omar Touqan entitled, "Analysis of Non-Yielding Basement Wall Adjacent to Strip Footing," submitted in May 2016. Thesis advisor is Dr. Magdi El-Emam. Soft and hard copy available.